১৫ই আগস্টের সামরিক অভ্যুন্থান মুজিব হত্যা ও ধারাবাহিকতা : একটি সম্পূর্ণ ভিন্নধর্মী বিশ্লেষন - হাসান উজ্জামান
Critical analysis of the circumstances in which Sheikh Mujibur Rahman, 1922-1975, first president of Bangladesh, was assassinated, and the rise of military power in Bangladesh, in August 1975.